Representasi Obsesi Kecantikan Perempuan dalam Film Lampir (2024) Karya Kenny Gulardi - Listina Tunggal Dewi; Ridma Meltareza; Detya Wiryani (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The purpose of this study is to identify the construction of beauty obsession through narrative and character portrayal, to describe the symbols and visual elements that construct meanings of beauty and power, and to interpret the meanings formed in relation to audience understanding of social pressure and women’s self-image. This study employed a qualitative approach using descriptive-interpretative media text analysis, grounded in Stuart Hall’s theory of representation (1997), which examines meaning at three levels: denotative, connotative, and mythical. Data were collected through audio-visual documentation in the form of repeated observations of the film, as well as literature review, and were analyzed through the stages of identification, interpretation, and contextualization. Data validity was ensured through triangulation of sources, techniques, and time. The findings reveal that beauty obsession is constructed through two complementary character trajectories, namely Mak Lampir as an extreme representation of beauty as a source of existence and Agnes as a representation of beauty insecurity. These constructions are reinforced by systematic visual symbols such as mirrors, lighting contrasts, and color schemes that consistently establish a hierarchy between women who are considered beautiful and those who feel they do not meet such standards. This study concludes that unrealistic beauty standards not only oppress women who fail to attain them, but also destroy those who succeed in achieving them, suggesting that beauty as the sole measure of women’s worth ultimately produces emptiness rather than happiness. These findings provide a reflective contribution for the film industry and audiences in reading the representation of women’s beauty more critically.